SIFAT FISIK DAN SIFAT MEKANIK PAPAN PARTIKEL BERDASARKAN PERBEDAAN GRADE DI PT. BARITO PACIFIK Tbk - Muhammad Ramadhani; Lusita Wardani; Lusyiani Lusyiani (Jurnal Sylva Scienteae, 2020)
PT Barito Pacifik Tbk is a company engaged in the forestry industry that focuses on the processing of waste wood in the form of sawdust, sebetan, pieces and wood shavings. The resulting product is a particle board. The purpose of this research is to test the physical properties and mechanical properties based on different grades of particle board and to know the quality of particle board based on physical and mechanical properties. Design analysis used (RAL) with 3 replications and 7 levels. Consisting of two factors: grade A and grade B. Water content, density, thickness development, bending congestion, broken firmness, firmness of screws, tilt perpendicular straightness Surface is the type of parameters tested. The results of this study indicate that grade A and grade B have no significant effect. Particle board produced by PT Barito Pacifik Tbk still exist under SNI 03-2105-2006. Overall that meets the SNI that is from particle board testing is the density, moisture content, thickness development, MOE, MOR and adherence firmness but on the firmness of screws unplug does not meet SNI 03-2105-2006.Keywords: Wood waste, physical properties and mechanical properties, particle board